Oscillations in Neutral Winds Observed by GOCE. Issue 17 (5th September 2020) - Dhadly, Manbharat S.; Emmert, John T.; Jones, McArthur; Doornbos, Eelco; Zawdie, Kate A.; Drob, Douglas P.; Conde, Mark G.
Abstract: This study explores intra‐annual oscillations (IAOs) in upper thermospheric winds using GOCE cross‐track wind measurements between 70°S and 70°N. Due to the Sun‐synchronous dawn‐dusk orbit of GOCE, the cross‐contamination between seasonality and local time variations in winds is minimal, which makes it a unique space‐based data set to extract IAOs and study their latitudinal variation. Our analysis reveals that the annual (AO), semiannual (SAO), and terannual (TAO) oscillations are robust features in thermospheric winds. The AO is strongest at middle latitudes; SAO and TAO amplitudes increase with increasing latitude. The latitudinally averaged amplitudes of the AO, SAO, and TAO for dusk/dawn are 30.0/35.0, 8.5/11.3, and 6.0/6.6 m/s, respectively. The phase of AO reverses around the equator. SAO and TAO phases vary with latitude but do not reverse like the AO. For both the SAO and TAO, the average phase at dusk and dawn differs by ∼30 days. Plain Language Summary: The Earth's upper atmosphere (90–500 km) exhibits many well‐known seasonal oscillations, but the presence of such seasonal oscillations (order higher than annual) in global upper atmospheric neutral winds has not been clearly established. Understanding the characteristics and sources of these oscillations in the ionosphere and thermosphere is necessary to accurately forecast the Earth's upper atmosphere. Most of the widely available wind databases are either not suitable for such a study due to cross‐contamination of seasons and local time in their measurements or have limited spatial or seasonal coverage. However, because of GOCE's near Sun‐synchronous orbit, the cross‐contamination between local solar time and seasonal variations is minimal, which makes it a unique data set to study the seasonal behavior of upper thermospheric winds at least around the dawn and dusk periods. Thus, in this study we utilized GOCE wind data to quantify the annual, semiannual, and terannual oscillations in upper thermospheric winds. Key Points: The cross‐contamination between seasonality and local solar time variations is minimal in GOCE data AO, SAO, and TAO oscillations are robust features in neutral winds, all having appreciable amplitudes that vary as a function of latitude The AO is strongest at middle latitudes, and SAO and TAO amplitudes increase with increasing latitude on both sides of the equator